The Influence of POS on Employee Performance with Job Satisfaction as a Mediator - Putri, Kartika; Haryadi, Haryadi; Anggraeni, Ade Irma (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
This study conducted a research on variable of POS, and employee performance as well as job satisfaction as a mediation variable. This research is quantitative research. The subjects of this study are researchers at LIPI Center for Oceanographic Research. Primary data in this study was obtained directly from the respondents through questionnaires. Sample determination method used in this research is simple random sampling method with saturated sampling technique using Slovin method. Response rate in this study is 92.5%, so the questionnaires distributed were as much as 87 questionnaires. The analysis technique used is Partial Least Square model estimation and the mediation test used Sobel test. The results of this study indicate that POS has a significant positive effect on job satisfaction and employee performance, job satisfaction has a significant positive effect on employee performance, and job satisfaction mediates the influence of influence of POS on performance.